Energy Analysis and Eksergi on Combine Cycle Power Plant Gas and Steam (CCPP) Sengkang - Muhammad Agung (Teknik Mesin "TEKNOLOGI", 2010)
Analyze the main components of combine cycle power plant gas and steam with energy analysis is not able to present comprehensive analysis if not accompanied by eksergi analysis. Eksergi analysis can calculate the energy lost by the nature of irreversibilitas process within a system, which is not calculated by the energy analysis calculations based on the law of conservation of mass and energy. This research aims to find out: (1) performance of CCPP Sengkang component with energy analysis (2) performance of CCPP Sengkang component with analysis eksergi (3) exergy destruction due exergy irreversible process in the main component (4) comparison of exergy destruction and irreversibility, and (5) performance of each component of the boiler through Grassman and Sankey diagrams. The research was conducted on the unit CCPP Sengkang owned by PT Energi Sengkang which located in the village Patila, Wajo district, South Sulawesi province. The method used in this study is the method of observation and recording of direct observation on each parameter is required when the CCPP Sengkang to operate at maximum load (135 MW). The results showed the efficiency of its main components with the energy analysis of the combustion chamber (93.74%), boiler (87.42%), turbine (56.19%) and compressor (41.43%), while with the exergy analysis obtained the boiler (73.26%), combustion chamber (66.43%), compressor (35.90%), and turbine (33.57%). To the greatest destruction eksergi losses in the system of CCPP Sengkang is obtained 58412.06 kW or 35.79% on combustion chamber. Keywords: exergy, energy, and power plant.